THE DEVELOPMENT OF LESSON PLAN TO APPLY DIRECT INSTRUCTION MODEL AND MULTISIM SOFTWARE TO IMPROVE SCIENCE PROCESS SKILL OF VOCATIONAL SCHOOL STUDENTS - Eki Pristiyanto; I.G.P. Asto Buditjahjanto (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
The aim of this research is to describe the validity of high-quality lesson plan to apply the direct instruction model equipped with Multisim software to improve the science process skill of Vocational School student. This research is development research where in the research design the development of lesson plan adapted from 4D models (four D models). Further, in order to get the validity of developed lesson plan, it needs to perform the validation by the experts. This research shows that validation results of the developed lesson plan are obtained final average scores as follows: score 3.75 categorized highly valid and percentage of agreement in the assessment that given by three validators is 96.82% for Syllabus. Score 3.72 categorized highly valid and percentage of agreement in the assessment given by three validators is 95.15% for the scenario of Lesson Plan. Score 3.79 categorized highly valid and percentage of agreement in the assessment that given by three validators is 95.33% for Work Sheet. Score 3.47 categorized valid and percentage of agreement in the assessment that given by three validators is 87.34% for Assessment Sheet, and score 3.67 categorized highly valid and percentage of agreement in the assessment that given by three validators is 94.26% for Text Book.